Impact of Maternal Folate Deficiencies on Early Neurological Development: A Narrative Review - Joshua T Emmerson; Nafisa M Jadavji (Mazandaran University of Medical Sciences, 2016)
Context Folates are B-vitamins that cannot be generated de novo and are therefore obtained from the diet. In the brain, these vitamins are involved in nucleotide synthesis, DNA repair, lipid metabolism, methylation and neurotransmitter synthesis. It is well established that adequate levels of maternal folates are required for closure of the neural tube within the first month of pregnancy, however, it is not clear whether maternal folates are needed throughout pregnancy for brain development and whether they influence offspring neurological function after birth. The aim of this review is to outline current literature from epidemiological and animal model studies that shows maternal supplementation of folates throughout pregnancy does indeed affect offspring neurological function after birth. Evidence Acquisition A Medline search was performed using the following mesh terms, maternal-fetal exchange, folic acid, offspring neurologic manifestations, methylenetetrahydrofolate reductase (MTHFR), embryology, and behavior. Results The studies described in the present review have reported that maternal deficiencies in folates during pregnancy result in changes in behavior as well as in blood and brain tissue in offspring, including altered methylation, including reduced levels of the global methyl donor S-adenosylmethionine (SAM), and increased levels of oxidative stress. Conclusions The data summarized here outlines the importance of adequate levels of folates throughout pregnancy to facilitate appropriate neurological development of offspring after birth.